Pervaporation of Aqueous Solution of Acetaldehyde Through ZSM-5 Filled PDMS Composite Membrane - 伍艳辉 谭惠芬 李佟茗 金源 (Chinese journal of chemical engineering, 2012)
Hydrophobic ZSM-5 zeolite filled polydimethylsiloxane （PDMS） composite membranes with Nylon micro-filtration membrane as the support layer were prepared to separate acetaldehyde from its aqueous solution. The composite membranes were characterized by Fourier transform infrared spectroscopy and X-ray diffraction. Their structural morphology and thermal stability were also examined. The swelling study showed that the composite membranes presented higher degree of swelling in aqueous solution of acetaldehyde than in pure water at 25℃,